Determinants of the Bid-Ask Spread On Forward Foreign Exchange Contracts Under Floating Exchange Rates - Cornell, W. B. (Journal of International Business Studies, 1978)
The bid-ask spread on forward contracts determines, in part, the effectiveness of the foreign exchange market as a vehicle for hedging exchange risk. The purpose of this paper is to try to explain the variation in the spread over time and across currencies by examining the costs and risks banks face when dealing in foreign exchange. The paper also attempts to define the proper risk measure for open forward position in foreign exchange.